Increased efficiency of a fuel cell using h-BN electrodes and Teflon polymer electrolyte [-C2F4-]n - Chitsazan, A.; Monajjemi, M.; Aghaei, H. (Revista de la Universidad del Zulia, 2020)
Graphene and h-BN have been theoretically simulated for hydrogen storage and oxygen diffusion in a single fuel cell unit. Obviously, the efficiency of the PEM hydrogen fuel cells was significantly related to the amount of H2 concentration, the water activities in catalyst substrates and the polymer of the electrolyte membranes, the temperature and the dependence of such variables in the direction of the fuel and air currents between the anode path and the cathode. The single PEM parameter has been estimated and the results show greater fuel cell efficiency using graphene sheets and h-BN. Maximum efficiency is observed with the stoichiometry of the 5H2, 5O2 and 3 C2F4 molecules during adsorption.